Natural deep eutectic solvent formulations for spirulina: Preparation, intensification, and skin impact - Wilsa, Laura; Leman-Loubiere, Charlotte; Bellin, Nicolas; Clement-Larosiere, Barbara; Pinault, Michelle; Chevalier, Stephan; Enguehard-Gueiffier, Cecile; Enguehard-Gueiffier, Cecile; Boudesocque-Delaye, Leslie
Microalgae are a sustainable source of bioactive compounds like carotenoids, free fatty acids and especially polyunsaturated fatty acids. The extraction of such nonpolar metabolites usually involved nonpolar or toxic solvent like methanol or hexane. We report the first screening of Natural Deep Eutectic Solvents for the extraction of pigments and free fatty acids from spirulina. Natural Deep Eutectic Solvent with a wide range of polarity was screened, and the resulting extracts were compared according to their pigment and free fatty acid contents. The extraction performance was increased, and various metabolite profiles were obtained. A Natural Deep Eutectic Solvent based on glycerol/glucose exhibited a wide range of metabolites, which ranged from polar phycobiliproteins to free fatty acids. Natural Deep Eutectic Solvent based on a fatty acid mixture demonstrated the highest selectivity towards free fatty acids. After intensification of the extraction process, 6 spirulina- Natural Deep Eutectic Solvent formulations and Natural Deep Eutectic Solvent alone were evaluated in terms of the effects on cutaneous inflammation induced by Staphylococcus aureus, as well on 4 bacterial species that are part of the skin microbiota. The glycerol/glucose formulation exhibited an anti-inflammatory effect on keratinocytes stimulated by S. aureus. Nonpolar Natural Deep Eutectic Solvent alone and formulations impacted bacterial viability, especially for S. aureus, thus providing a new approach for the regulation of skin microbiota or product preservation.
Keywords: DEEP EUTECTIC SOLVENT; MICROALGAE; ARTHROSPIRA PLATENSIS; FREE FATTY ACID; SKIN MICROBIOTA; INFLAMMATION